Good News for the Oppressed? Exploring the Spiritual, Political, and Intercultural Dimensions of Howard Thurman’s Philosophy - Aizaiah G. Yong (Religions, 2024)
This paper centers on the godfather of the civil rights movement, Howard Thurman, and his most influential work, “Jesus and the Disinherited”, as a pre-eminent text into early 20th century intercultural philosophy. Building upon Kipton Jensen’s analysis in “Howard Thurman: Philosophy, Civil Rights, and the Search for Common Ground”, this presentation will reframe Howard Thurman’s unique philosophy as one that integrates spirituality, interculturality, and critical social analysis. It is well known that Thurman’s treatise on the oppressed was carried in the pocket of Rev. Dr. Martin Luther King Jr. throughout the civil rights movement for the ways it empowered nonviolent resistance for those marginalized by the dominant culture of the United States, which was (and still is) built on racism, military violence, and class-based oppression. This paper advocates that Thurman came to his philosophical conclusions through deep engagement with various cultural and philosophical traditions, most notably the Hindu spiritual–political paradigm of Mahatma Gandhi, and sought to harmonize these insights for African Americans in the USA. By investigating the intercultural foundations of “Jesus and the Disinherited”, this paper will encourage scholars to explore how interculturality enriched Thurman’s philosophy and how this fostered a more expansive vision of community in pluralistic societies. This article traces the roots of the development of “Jesus and the Disinherited”, looking back to presentations Thurman gave as early as 1922, concluding with the publication of his book in 1949. And via this study, we will see the progression of Thurman’s ideas and the impacts interculturality had on his philosophy and vision for social justice.